Between convention and originality. About Pacierz Ślęzakow do Pana Boga na Prusakow - Szagun, Dorota (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
This article concerns an eighteenth-century piece entitled Pacierz Ślęzakow do Pana Boga na Prusakow. The basis of the analysis is a text written probably after 1742, at a time when Silesia was under Prussian rule. The piece is an example of popular and socially engaged literature. Pragmatic considerations have led to a highly conventionalized text, referring to the typical kind of prayer on the one hand; on the other hand, the original text, with clear temporal and socio-ideological references. The author expresses the conviction that the incorporation of the genre pattern of The Our Father prayer to a poetic piece derives both from the reliance on the authority and prestige of prayer and on minimizing the effort to receive the prayerful character of the text, generation of the sense of ethnic and religious communion by referring to the well-known, and even strongly intermixed ritual, and thus through the transformation of linguistically individualized expression into a collective voice.